Determinación de la influencia de la actividad arrocera en los niveles de concentración de fosfatos en el río Indoche, Moyobamba, San Martín - Iberico Varas, Juan Miguel (2014)
The present study, involved in monitoring the parameter of Total Phosphorus at 08 points along the basin of the Indoche river, on a stretch of 70 km above basin from the mouth of the River Indoche on the Mayo River. The monitoring points were numbered from 01 to 08, being the point 01 the highest in the basin of the samplings considered, and the point 08, the lowest point of the basin, that is to say in the river mouth ofthe river fudoche in the Mayo River. There has been periodic monitoring in three hours of the day. A first monitoring at 06:30 hrs, another at 12:30 hrs anda third at 18:30 hrs, to contrast the concentrations of phosphates throughout the day. The results show that there is a variation of the Phosphates concentrations both point to point monitoring, as in the hour. These results indicate that as are monitored basin below, the phosphates concentrations are on the rise, this coinciding with that the lower the basiu, increased human activity there is, with this the agricultural fields are increasing in quantity. According to the results, the point where lower concentrations of phospbates is obtained, was in the top ofthe basin, that is to say at the point ofmonitoring 01, with an average of 0,037 ppm, and the point where greater concentratiou was in the 07, with an average of 0,453 ppm, and the point of monitoring 08, corresponding to the lowest and the same that is the mouth ofthe river Indoche on the Mayo River, was of0,437 ppm. This result was less than the penultimate point, due to the concentration decreases when diluted in a greater flow rate to joín the two rivers. As for the schedules, there was obtained as result that to them 06:30 hrs, ·the average concentration was of 0.251 ppm, the m~or concentration was seen to the balf day by 0.259 ppm, and the minor always at 18:30 hrs by 0.228 ppm. All the results, do not exceed 0.5 ppm according to the ECA approved through the DS 002-2008-MINAM, for waters. of the type IV suitable for conservation of aquatic ecosystems, therefore, it is concluded if there is an influence of the rice crops in the phosphate levels in the Indoche river, but that these levels, do not exceed the concentrations that current legislation sets, but that there is a tendency to continue to increase, according to the agricultural area continues to expand. Key words: Phosphates concentrations, agricultura! fields. JR. PROLONGACIÓN 20 DE ABRIL SIN- TELEF. 042